2018
DOI: 10.1088/1612-202x/aac5c8
|View full text |Cite
|
Sign up to set email alerts
|

Power scaling of narrow-linewidth mid-IR spherical microlasers

Abstract: We discuss issues re: power scaling of mid-IR Er:ZBLAN spherical microlasers and demonstrate achievement of near-milliwatt power levels from a narrow-linewidth (Δλ < 50 pm) 2.71 µm laser source based on an Er:ZBLAN microlaser.Narrow linewidth mid-infrared (MIR) lasers are important sources for trace level detection of a broad range of molecular species by spectroscopic methods [1,2]. For this application, interband and quantum cascade semiconductor lasers (ICLs and QCLs) --of distributed feedback (DFB) design … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[6] Behzadi et al reported a 2.71-µm microsphere laser based on an Er 3+ -doped ZBLAN glass. [7][8][9] Chalcogenide glasses are also promising base materials for MIR microsphere lasers. [10] Compared to the tellurite and ZBLAN glasses, chalcogenide glasses have much wider transmission windows and thus can potentially support more operation wavelengths for microsphere lasers.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Behzadi et al reported a 2.71-µm microsphere laser based on an Er 3+ -doped ZBLAN glass. [7][8][9] Chalcogenide glasses are also promising base materials for MIR microsphere lasers. [10] Compared to the tellurite and ZBLAN glasses, chalcogenide glasses have much wider transmission windows and thus can potentially support more operation wavelengths for microsphere lasers.…”
Section: Introductionmentioning
confidence: 99%